Polyelectrolyte Substrate Coating for Controlling Biofilm Growth at Solid–Air Interface. Issue 10 (18th March 2021) - Ryzhkov, Nikolay V.; Nikitina, Anna A.; Fratzl, Peter; Bidan, Cécile M.; Skorb, Ekaterina V.
Abstract: Because bacteria–surface interactions play a decisive role in bacteria adhesion and biofilm spreading, it is essential to understand how biofilms respond to surface properties to develop effective strategies to combat them. Polyelectrolyte coating is a simple and efficient way of controlling surface charge and energy. Using polyelectrolytes of various types, with different molecular weights and polyelectrolyte solutions of various pH provides a unique approach to investigate the interactions between biofilms and their substrate. Here, the formation of Escherichia coli biofilms at a solid–air interface is explored, whereby charge and interfacial energy are tuned using polyelectrolyte coatings on the surface. Cationic coatings are observed to limit biofilm spreading, which remain more confined when using high molecular weight polycations. Interestingly, biofilm surface densities are higher on polycationic surfaces despite their well‐studied bactericidal properties. Furthermore, the degree of polyelectrolyte protonation also appears to have an influence on biofilm spreading on polycation‐coated substrates. Finally, altering the interplay between biomass production and surface forces with polyelectrolyte coatings is shown to affect biofilm 3D architecture. Thereby, it is demonstrated that biofilm growth and spreading on a hydrogel substrate can be tuned from confined to expanded, simply by coating the surface using available polyelectrolytes. Abstract : Polycationic coatings are shown to encourage confined spreading of Escherichia coli biofilms at solid–air interface in static conditions. It is demonstrated that the effect of polyelectrolytes is caused by complex interactions at the substrate–biofilm interface and cannot be fully explained by the previously reported polycation toxicity.